2014
DOI: 10.1097/mjt.0b013e318217a609
|View full text |Cite
|
Sign up to set email alerts
|

On the Differences Between Ouabain and Digitalis Glycosides

Abstract: Digoxin and digitoxin are widely used in the treatment of heart diseases. The exact mechanism of action of these drugs has remained an enigma. Ouabain has become the standard tool to investigate the mode of action of cardiotonic steroids, and results with ouabain are regarded as generally valid for all cardiac glycosides. However, there are marked differences between the effects of ouabain and digitalis glycosides. Ouabain has a different therapeutic profile from digitalis derivatives. Unlike digitalis glycosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 56 publications
0
36
0
Order By: Relevance
“…In addition, at low concentrations binding of ouabain to NKA activates multiple signal transduction pathways [95, 96]. Recent research has confirmed the uniqueness of ouabain; supported by the fact that ouabain has a different mechanism of action to digitalis glycosides [97]. Experiments with extremely low concentrations (10 -8 M) of ouabain in isolated working rat hearts provide strong evidence that the cardioprotective effect of ouabain may be mediated by activation of transduction pathways rather than by inhibition of NKA [98].…”
Section: Ouabain Is Different From Digitalis Glycosidesmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, at low concentrations binding of ouabain to NKA activates multiple signal transduction pathways [95, 96]. Recent research has confirmed the uniqueness of ouabain; supported by the fact that ouabain has a different mechanism of action to digitalis glycosides [97]. Experiments with extremely low concentrations (10 -8 M) of ouabain in isolated working rat hearts provide strong evidence that the cardioprotective effect of ouabain may be mediated by activation of transduction pathways rather than by inhibition of NKA [98].…”
Section: Ouabain Is Different From Digitalis Glycosidesmentioning
confidence: 99%
“…Ouabain exerts its therapeutic effects already in low nanomolar and even picomolar concentrations. In addition, a critical analysis of the available data proposes that Strophanthus glycosides have a distinct different mode of action than Digitalis glycosides [97]. Digitalis glycosides mimic the effects of catecholamines, whereas Strophanthus glycosides counteract sympathetic activity.…”
Section: Ouabain Is Oats For the Starving Myocardiummentioning
confidence: 99%
“…The eighteen candidates in this report were selected from sixty credible leads by a scientific panel; they covered a range of potentially promising mechanisms of action against EBOV. Brief details of the compounds nominated for inclusion are outlined below: Ouabain: Originally used for the treatment of heart diseases [5], which has been demonstrated to reduce EBOV replication by around half when testing in vitro in a study looking into the viral protein 24 (VP24) protein and the interruption of cellular interacting proteins [6]17-DMAG: An inhibitor of heat shock protein 90 (HSP90), which has been shown to reduce in vitro EBOV replication [7]BGB324: An inhibitor of Axl receptor tyrosine kinase, which appears to be involved with Ebola virus entry into host cells [8]JB1a: An antibody therapy, targeting beta-1 integrins, which have been proposed to facilitate the entry of filoviruses; treatment of target cells with the JB1a clone reduced infection using a vesicular stomatitis virus (VSIV) pseudotyped with EBOV glycoprotein [9]Omeprazole and esomeprazole magnesium: Members of the benzimidazoles that may stop viral entry via clathrin-mediated endocytosis by raising the endosomal pH. Both compounds were shown to inhibit lentivirus-based pseudotypes expressing EBOV glycoprotein [10]…”
Section: Introductionmentioning
confidence: 99%
“…Ouabain: Originally used for the treatment of heart diseases [5], which has been demonstrated to reduce EBOV replication by around half when testing in vitro in a study looking into the viral protein 24 (VP24) protein and the interruption of cellular interacting proteins [6]…”
Section: Introductionmentioning
confidence: 99%
“…Despite the structural similarities between digoxin and ouabain, their intracellular effects are thought to be markedly different. 32,33 Unlike ouabain, digoxin is able to pass through the cell membrane whereby it binds to ryanodine receptors. 34 Once bound, Ca 2 + is released from the sarcoplasmic reticulum.…”
Section: Introductionmentioning
confidence: 99%